2013
DOI: 10.3171/2013.3.peds12525
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intracranial hypertension after cranial vault remodeling for nonsyndromic single-suture synostosis

Abstract: Object Delayed intracranial hypertension may occur after cranial vault remodeling for synostosis and may result in visual loss and developmental delay. Delayed intracranial hypertension is relatively common in children with syndromic, multisuture synostosis, but the incidence is poorly defined in children with single-suture nonsyndromic synostosis. This study evaluates the frequency of reoperation for delayed intracranial hypertension after single-suture synostosis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 29 publications
2
49
1
Order By: Relevance
“…In a smaller series of 47 patients with SC, Cetas and colleagues reported postoperative raised ICP in 5 patients (10.5%), 2 of whom had strip craniectomies with barrel staving and 3 an anterior two-thirds cranial vault reconstruction. 8 This rate more closely reflects that of this series. All of their patients presented with symptoms of raised ICP and 3 had papilledema.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a smaller series of 47 patients with SC, Cetas and colleagues reported postoperative raised ICP in 5 patients (10.5%), 2 of whom had strip craniectomies with barrel staving and 3 an anterior two-thirds cranial vault reconstruction. 8 This rate more closely reflects that of this series. All of their patients presented with symptoms of raised ICP and 3 had papilledema.…”
Section: Discussionmentioning
confidence: 60%
“…11,35,50 Consistent with the patient series of van Veelan et al and Cetas et al, we found that elevated ICP was diagnosed late, at least 2 years after primary surgery, with a mean at just under 4.5 years of follow-up. 8,47 This interval, along with the findings that only 1 patient had papilledema and that 4 children developed raised ICP on re-monitoring after a proven normal ICP, strongly suggests that the pathological rise in ICP we observed occurred after primary surgery. We have no evidence to indicate that an elevated ICP was present beforehand and persisted through the first corrective procedure to the time of diagnosis after surgery in any patients in this study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…13,28,45,47 However, it is difficult to infer anything directly from these observations without corresponding ICP data, because in the authors' and others' experience, raised ICP can occur after surgical corrective procedures. 9 Any resultant decline in neurocognitive function in affected individuals could mask an improvement in the overall group. Furthermore, there is contrary evidence that, after surgery, single-suture craniosynostosis patients are of normal intelligence during school-age years and patients with a proven raised preoperative ICP experience improved neurocognitive functioning.…”
mentioning
confidence: 99%
“…Seven studies 2,7,[16][17][18][19]30,33 met inclusion criteria for analy sis of the primary outcome: incidence of IH after surgery confirmed by invasive ICP monitoring (Table 1). Addi tional studies that used alternate methods of confirmation of IH were excluded from the analysis but are reviewed in the discussion and included 4 studies using lumbar punc ture as confirmation of IH; 1,6,14,23 1 study using the pres ence of papilledema; 4 and 2 studies used a combination of ICP monitoring, clinical symptoms, and the presence of papilledema 25,28 (Table 2).…”
Section: Results General Characteristicsmentioning
confidence: 99%